Reading the Symptoms of Equality: Rancière’s symptomatology - Völker, Jan (Filozofski vestnik, 2016)
Rancière starts his book Disagreement from a peculiar relation between politics and philosophy: There is no proper object named politics, and philosophy does not have a language of its own that distinguishes it from literature and other discourses. Politics is rather the outcome of the contention of two kinds of logics, and philosophy has to follow the traces of its suspensions. Fundamentally, politics produces suspensions of the understanding or expresses the absence of any natural unity of time and space. Philosophy has to turn into a symptomatology to be able to read these traces, and at the same evidently reproduces them in its own discourse. This torsion of philosophy is followed through the three different notions of the symptom that Rancière develops: in relation to modern politics, in relation to the philosophical text, and in relation to the literary.